Estudo teórico de nano sistemas de azulenos: azulfenos, ANTs, poliazulenos e polinaftalenos - Costa, Alexandre (2020)
Azulene-based nanographene-like materials are predicted and studied to reveal the molecular properties of these new materials. C48H18/(G-48), C68H22/(G-68), and C88H26/(G-88) nanographenes and their isomers based on azulene molecule (azulphene) as A-48, A-68, and A-88 were studied to infer general properties for large azulphene systems. Nanotubes from azulphenes are also obtained and studied. The isoelectronic graphene and azulphene materials have significant differences concerning, e.g., electric dipole, aromaticity, bond length, and bond stress. In the present studies, it was used the Density Functional Theory (DFT) and including the version of Grimme´s D dispersion for the different spin multiplicities: singlet close-shell (CS) and open-shell (OS), triplet, and quintet. For example, the ground-state of A-(48-68-88) structures is a singlet. The UV-visible spectra of all compounds exhibit maximum absorption peaks attributed to the electronic transition π→π*. The IR spectrum of G-88 and A-88 shows an intense set of absorption peaks in the range [600:1700 cm-1]. The following IR frequencies could be used as an indicator of azulphene structures: 1124, 1162, 1436, 1542, and 1597 cm-1. The azulphene sheets have a non-uniform distribution of the electron density, unlike graphene systems, which makes them promising candidates for regioselective chemical modification. The nucleus independent chemical shift calculations show that the five-membered rings are aromatic, and the seven-membered rings are anti-aromatic similar to azulene molecule. Our study also showed that smaller diameter tubes based on azulene (C57NTs) might be more stable than their conventional C6NTs isomer. The geometries, the electronic structures and the aromaticity of the [n]-azulene and [n]-naphthalene polymers were studied, by using the Density Functional Theory (DFT) and the Møller–Plesset (MP2) Pertubation Theory, for the different multiplicities (M=2S+1): singlet (S=0, closed and open shell), triplet (S=1) and quintet (S=2). The ground-states of the [n]-azulene polymers were a singlet (closed shell) for any values of n (n≤10). The ground-states of the [n]-naphthalene polymers were a singlet (closed shell) for n≤6 and triplet for 7≤n≤10. The electric dipole moment of the odd [n]-azulene polymers varied with the length of the polymer chain, while exhibiting a local minimum for [5]-azulene. The dipole of the even [n]-azulene and the (even and odd) [n]-naphthalene polymers were null by symmetry, essentially as a result of the non-polar structure of the azulene dimer and the benzene molecule. The [n]-azulene polymers could be considered as semiconductors, since for the large chain, the HOMO-LUMO gap was estimated at 0.70 eV. The large naphthalene polymers perhaps reached zero gaps. All of the polymers had electronic transition peaks in the visible region and their maximum was red-shifted for the increasing chains. The nucleus independent chemical shift (NICS) calculations have shown that ring tension was an important factor in the aromaticity loss, as shown, for example, for the flat, the cycle, and the Möbius strip [20]-polymers. The Aromatic Stabilization Energies (ASEs) that were based on the homodesmotic and isodesmic reactions were also obtained.